Case study: water crisis in the Metropolitan Region of São Paulo – 2013-2015 - Jacobi, Pedro Roberto; Cibim, Juliana Cassano; Souza, Alexandre Nascimento (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2015)
The decrease of the rain indexes in the southeast region of Brazil presented a pre- dictable scenario of water scarcity for the year 2015. Due to the denial of the pos- sible crisis, water resources governance was affected. The critical situation and the slowness of effective proposals to minimize the crisis, turn the Metropolitan Region of São Paulo, a critical area as to water quantity and quality. From the observation of this new condition, this article, besides contextualizing the crisis, presents propo- sals for the governance of water resources in the State of São Paulo.